Kontrol Fuzzy Logic Dalam Menentukan Produksi Air Demin Pada PLTU - Sumardi SPd. Sadi; Sri Mulyati (Journal of Electrical Engineering and Computer (JEECOM), 2021)
Demineralized water production that is not in accordance with the supplies needed in a power plant results in less effective and efficient operation of the power plant. This requires careful control. The control system can use a fuzzy logic-based control system. In this article, we describe the trial of controlling the production of demin water with the aim of determining the production of electricity for consumer needs. The method used is fuzzy logic control. The result can adjust the supply of demin water according to the available stock and the number of requests. The electricity production resulting from fuzzy calculations in generating electricity production is the Tsukamoto method of 698.3 MW/day, the Mamdani method of 254.16 MW/day, and the Sugeno method of 537.3 MW/day.